Hegel zum 250sten: Neues aus der Forschung - Koch, Anton Friedrich (Philosophische Rundschau, 2021)
In this collective review, seven books on Hegel are discussed. Following Hegel's internal chronology, we begin with a voluminous study on the Phenomenology of Spirit by Robert Brandom. This is followed by two books on the Science of Logic, first a commentary on the logic of being by Pirmin Stekeler, then an interpretation of the entire Logic by Robert Pippin. After the Logic comes the Realphilosophie, represented by Terry Pinkard's critical examination of Hegel's philosophy of history. The review concludes with books on Hegel's »system« as a whole, first a book for the audience of Hegel scholars by Walter Jaeschke, then a specialist book in the broader philosophical sense by Günter Zöller, and finally a book aimed at the general audience by Sebastian Ostritsch.Robert B. Brandom: A Spirit of Trust. A Reading of Hegel's Phenomenology. Cambridge (MA) und London 2019: The Belknap Press of Harvard University Press. XIV, 836 S. - Walter Jaeschke: Hegels Philosophie. Hamburg 2020: Felix Meiner Verlag. 431 S. - Sebastian Ostritsch: Hegel. Der Weltphilosoph. Berlin 2020: Propyläen (Ullstein Buchverlage). 315 S. - Terry Pinkard: Does History Make Sense? Hegel on the Historical Shapes of Justice. Cambridge (MA) und London 2017: Harvard University Press. 272 S. - Robert B. Pippin: Hegel's Realm of Shadows. Logic as Metaphysics in the Science of Logic. Chicago 2019: The University of Chicago Press. VIII, 339 S. - Pirmin Stekeler: Hegels Wissenschaft der Logik. Ein dialogischer Kommentar. Band I: Die objektive Logik. Die Lehre vom Sein. Qualitative Kontraste, Mengen und Maße. Hamburg 2019: Felix Meiner Verlag. 1296 S. - Günter Zöller: Hegels Philosophie. Eine Einführung. München 2020: Verlag C. H. Beck. 127 S.